Operations strategy and supply chain management: A Brazilian case study - De Sousa Jabbour, Ana Beatriz Lopes [UNESP] (My University, 2012)
The objective of this study is to understand how an assembly company, that is considered a focal company in the chain of Brazilian white goods sector, can influence the supply chain management established with its first tier suppliers. This is an exploratory qualitative study in which the information was gathered through direct observations, documents' retention, and data from interviews held with management-level employees of the sales and product development areas of the focal company and of the production area of the suppliers' companies. This study indicates that the operations strategy of the focal company influences the supply chain management and that the common business processes shared by its suppliers are a way to verify the truth of such statement. The suppliers cooperate closely with the focal company when complementing their business processes and consequently supporting the company to pursue its operations strategy. A set of mechanisms to aid the comprehension of how the operations strategy can affect the business processes and therefore to achieve the result of this research were adopted. © EuroJournals Publishing, Inc. 2012.
Keywords: Brazil; Business processes; Operations strategy; Supply chain management